Broadcast Spawning Coral Mussismilia hispida Can Vertically Transfer its Associated Bacterial Core - Leite, Deborah C. A.; Leão, Pedro; Garrido, Amana G.; Lins, Ulysses; Santos, Henrique F.; Pires, Débora O.; Castro, Clovis B.; van Elsas, Jan D.; Zilberberg, Carla; Rosado, Alexandre S.; Peixoto, Raquel S. (Frontiers in Microbiology, 2017)
The hologenome theory of evolution (HTE), which is under fierce debate, presupposes that parts of the microbiome are transmitted from one generation to the next [vertical transmission (VT)], which may also influence the evolution of the holobiont. Even though bacteria have previously been described in early life stages of corals, these early life stages (larvae) could have been inoculated in the water and not inside the parental colony (through gametes) carrying the parental microbiome. How Symbiodinium is transmitted to offspring is also not clear, as only one study has described this mechanism in spawners. All other studies refer to incubators. To explore the VT hypothesis and the key components being transferred, colonies of the broadcast spawner species Mussismilia hispida were kept in nurseries until spawning. Gamete bundles, larvae and adult corals were analyzed to identify their associated microbiota with respect to composition and location. Symbiodinium and bacteria were detected by sequencing in gametes and coral planula larvae. However, no cells were detected using microscopy at the gamete stage, which could be related to the absence of those cells inside the oocytes/dispersed in the mucus or to a low resolution of our approach. A preliminary survey of Symbiodinium diversity indicated that parental colonies harbored Symbiodinium clades B, C and G, whereas only clade B was found in oocytes and planula larvae [5 days after fertilization (a.f.)]. The core bacterial populations found in the bundles, planula larvae and parental colonies were identified as members of the genera Burkholderia, Pseudomonas, Acinetobacter, Ralstonia, Inquilinus and Bacillus, suggesting that these populations could be vertically transferred through the mucus. The collective data suggest that spawner corals, such as M. hispida, can transmit Symbiodinium cells and the bacterial core to their offspring by a coral gamete (and that this gamete, with its bacterial load, is released into the water), supporting the HTE. However, more data are required to indicate the stability of the transmitted populations to indicate whether the holobiont can be considered a unit of natural selection or a symbiotic assemblage of independently evolving organisms.